A randomised controlled trial to compare the efficacy of preinduction with mifepristone 12 hours versus 24 hours prior for second trimister pregnancy termination - Patil, Neelamma Girish; Gupta, Priyanka; Hittinhalli, Megha D.; Mudanur, Subhaschandra R.; Tehalia, Manpreet Kaur J.; Nemagouda, Aruna S.; Kori, Shreedevi S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Since the second trimester termination of pregnancy is on rise due to the detection of anomalies, this study aims to provide a safe regimen with respect to efficacy, side effects and acceptability for second trimester pregnancy termination. Methods: It is a randomized controlled trial, conducted on 48 cases at BLDE Medical college, Vijayapur, Karnataka. They were divided into two groups; all patients were given mifepristone 200mg orally followed by misoprostol 400mcg vaginally after 12 hours in group I and 24 hours in group II respectively. Subsequent doses were decided depending on the Bishops score. Results were analyzed in terms of induction-abortion interval and dosage of misoprostol. Results: The mean induction abortion interval was 563.9 minutes (9.3hrs) in group I and 714.6 minutes (11.9hrs) in group II; but was statistically not significant (p value 0.611) The total dose of misoprostol used was 783.3mcg in group I compared to 550mcg in group II, but was statistically not significant. The success rate was 100% in both the groups as none of them had incomplete abortion. There were no cases of uterine rupture, infection, need for check curettage and laparotomy. Conclusions: Our study proves that the interval between mifepristone and misoprostol can be safely reduced to 12 hours without affecting the efficacy. But in gestational age <16 weeks and primigravida 24 hours interval may be of benefit. Both the regimens were 100% successful.